Stereotype Threat and Perceptions of Family-Friendly Policies among Female Employees - von Hippel, Courtney; Kalokerinos, Elise K.; Zacher, Hannes (Frontiers in Psychology, 2017)
In their efforts to recruit and retain female employees, organizations often attempt to make their workplaces “family-friendly.” Yet there is little research on how women view family-friendly policies, particularly women who experience gender-based stereotype threat, or the concern of being viewed through the lens of gender stereotypes at work. Pilot research with female managers (N = 169) showed that women who experienced stereotype threat perceived more negative career consequences for utilizing family-friendly policies. We then conducted two studies to further probe this relationship. Study 1 replicated the relationship between stereotype threat and the perceived consequences of utilizing family-friendly policies among women who recently returned to work after the birth of a child (N = 65). In Study 2 (N = 473), female employees who reported feelings of stereotype threat perceived more negative consequences of utilizing family-friendly policies, but they also reported greater intentions to use these policies. Our findings suggest that female employees are susceptible to stereotype threat, which in turn is associated with more negative views of family-friendly policies. Thus, the mere provision of such policies may not create the kind of family-friendly workplaces that organizations are attempting to provide.